Soft Drink Influence on Margin Integrity in Composite Resin Restorations - Lafuente DDS, MS, Jose; Abad DDS, Karol (Odovtos - International Journal of Dental Sciences, 2015)
The purpose of this study was to evaluate the effect that certain previously selected soda drinks could have on the integrity of the margins of composite restorations made on 25 human teeth, where the margins were placed both on enamel and dentin. Specimens were divided in different groups (n=5) to be exposed to soft drinks 30 minutes a day for 30 days. Selected drinks were: Coca Cola, Coca Cola Zero, Squirt, Gladiator and water. SEM pictures were taken at the beginning and at the 30 day mark. Data were compared and analyzed using Kruskal-Wallis. Results showed changes in color both in enamel and in dentin, as well as pigmentation of the composite resin qith the use of Coca Cola and Coca Cola Zero. This last one had the biggest negative impact on the margins of the resotrations, both on enamel and dentin, though this canges were not statistically significant. All soft drinks produced some damage to the margins which went from a small change barely detectable, up to a complete loss of integrity, these effects were not statistically significant among drinks.